50.3k views
1 vote
Solve. ln(–x + 1) – ln(3x + 5) = ln(–6x + 1) –0.67 or 2–1.58 or 0.14–0.14 or 1.58–2 or 0.67

User Haltabush
by
4.8k points

1 Answer

3 votes

We have


\ln \mleft(-x+1\mright)-ln\mleft(3x+5\mright)=ln\mleft(-6x+1\mright)

We need to simplify by applying logarithms rules


\ln \mleft(-x+1\mright)=ln\mleft(-6x+1\mright)+ln\mleft(3x+5\mright)
ln(-x+1)=\ln ((-6x+1)(3x+5))

Then we apply the exponential on both sides


-x+1=(-6x+1)(3x+5)

We simplify


18x^2+26x-4=0

Then we solve the second equation degree with the general formula


x_(1,2)=\frac{-b\pm\sqrt[]{b^2-4ac}}{2a}

where

a=18

b=26

c=-4

we substitute the values


x_(1,2)=\frac{-26\pm\sqrt[]{(26)^2-4(18)(-4)}}{2(18)}


x_(1,2)=\frac{-26\pm2\sqrt[]{241}}{36}

We reduce and the solution is


x_1=\frac{-13+\sqrt[]{241}}{18}=0.14
x_2=\frac{-13-\sqrt[]{241}}{18}=-1.58

ANSWER

–1.58 or 0.14

User Yavoh
by
4.3k points